(untitled) (Biological Sciences - PJSIR, 2025)
Consequent from increasing demand for amylase enzyme in the food industry, this study assessed the amylase production potentials of lactic acid bacteria (LAB) isolated from wheat sourdough. LAB were isolated from wheat sourdough samples and screened for amylolytic ability using the plate assay method. Isolates that were amylolytic were characterized and identified using standard methods. Submerged fermentation was carried out using the amylolytic lactic acid bacteria (ALAB) isolates at 30°C for 120 h. Reducing sugar yields and amylase activity were determined using the 3, 5-dinitrosalicylic acid method. The lactic acid bacteria isolates and their occurrences were as follows: L. plantarum 3(27.3%), L. brevis 3(27.3%), L. fermentum 2(18.2%), L. pentosus 1(9%) L. mesenteroides 1(9%) and P. pentosaceus 1(9%). A total of 11 isolates exhibited amylolytic activity with zones of starch hydrolysis in the range of 18-46 mm. L. plantarum TM3 and L. brevis KT1strains produced the highest reducing sugar concentrations (0.63mg/mL and 0.61 mg/mL respectively). Peak amylase activities of the ALAB isolates were observed at 24 h incubation time and ranged from 8.76 to 30.67 µmol/min/mL with L. plantarum TM3 and L. brevis KT1strains recording the highest amylase activities of 30.67 µmol/min/mL and 30.20 µmol/min/mL respectively. Findings from this study show that wheat sourdough is a good source of amylase-producing LAB strains such as L. plantarum TM3 and L. brevis KT1that could be exploited in starch degradation processes especially in the food industry.